EFFECT OF STUDENTS PERCEPTION OF PROFESSIONAL COMPETENCE OF TEACHER STUDENT LEARNING OUTCOMES IN SUBJEC THISTORY IN SMA STATE 2 BANGKO ROKAN HILIR - Ayu Lestari Lestari; Isjoni '; Tugiman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Education is a process of conscious effort and deliberately to increase the value of a person's behavior or society, from the particular circumstances kesuatu good condition. The purpose of this study was (1) to determine the student's perception about the professional competence of teachers in the Course of History at SMAN 2 Bangko Rokan Hilir. (2) to determine how the learning outcomes of students at SMAN 2 Bangko Rokan Hilir. (3) to know how to influence the perceptions of students about the professional competence of the Learning Outcomes in SMAN 2 Bangko Rokan Hilir. The method in this study is the use of quantitative methods. The population in this study were 254 students, the sample used in this study were 38 students. The collected data was then analyzed using percentages as a preliminary analysis and subsequent analysis using statistical analysis of product moment. While the learning outcomes of students who achieve a complete 28 students who did not complete 10 students. The hypothesis of this study is that there is a positive influence between the professional competence of teachers on student learning outcomes in subjects of history at SMAN 2 Bangko Rokan Hilir. In accordance with the statistical tes tproduct moment that I did it prove that r xy (r count) of 0.69 while the value t table(5%) (df =38-2=36) t table value of 0.32. Because t count greater than table or 0.69>0.32. Thus the hypothesis which states that"there is a positive influence between the professional competence of teachers with learning outcomes" is acceptable. The resulting determinant coefficient of r2=0.692=0.476=47.61%, it can be seen that the professional competence of teachers to the learning outcomes of 47.61%, the remaining 52.39% is influenced by other variables that are not addressed in this study.Keywords: Student Perceptions of Teachers' Professional Competence and Learning Outcomes.